Selecting students from low income family using analytical hierarchy process based on linguistic hedges - Zamali Tarmudi,; Ung, Ling-Ling; Nasrah Naharu,; Tammie C. Saibin, (Penerbit Universiti Kebangsaan Malaysia, 2013)
In this paper, we propose a new method for selecting students from low income family, namely Mengubah Destini Anak Bangsa (MDAB) programme by analytical hierarchy process based on linguistic hedges. It focuses on utilising the linguistic hedges for decision-makers (DMs)to make their judgement for weighting purposes. Two linguistic hedges, the concentration and dilation are used to measure the importance of relative weight for each criterion. Meanwhile, the group of DMs viewpoints is used to build the membership functions towards deriving the entire criterion performance scores. Then, the maxmin operator and sorting the results by descending order are applied to determine the best alternative and ranking process, respectively. A numerical example related to Universiti Teknologi MARA (UiTM) MDAB students’ selection is presented to demonstrate the applicability of the proposed method. It is found that the method is successful in dealing with situations which are relevant to the university concern, thus can facilitate the DMs to make a decision in a simple and systematic manner.